Rapid room-temperature synthesis of ultrasmall cubic Mg–Mn spinel cathode materials for rechargeable Mg-ion batteries. Issue 62 (8th November 2019) - Kobayashi, Hiroaki; Yamaguchi, Kazuya; Honma, Itaru
Abstract : An ultrasmall cubic Mg–Mn spinel obtained by an alcohol reduction process is demonstrated as a cathode candidate for rechargeable Mg-ion batteries. Abstract : Reducing the particle size of cathode materials is effective to improve the rate capability of Mg-ion batteries. In this study, ultrasmall cubic Mg–Mn spinel oxide nanoparticles approximately 5 nm in size were successfully synthesized via an alcohol reduction process within 30 min at room temperature. Though the particles aggregated to form large secondary particles, the aggregation could be suppressed by covering the particles with graphene. The composite exhibited a specific capacity of 230 mA h g −1, and could be cycled more than 100 times without any large capacity loss even at a moderate current density with the Mg(ClO4 )2 /CH3 CN electrolyte.